The Effect of Interval Training and Continuous Running on Improving the Aerobic Capacity of Youth Football Players - Rizkya Ananda Firdaus; Mona Fiametta Febrianty; Oktoviana Nur Ajid (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
This study aims to determine the effect of interval training and continuous running on increasing the aerobic capacity of adolescent football athletes and to compare the effectiveness of the two methods. This study used an experimental method with a two-group pretest–posttest design. The sample consisted of 30 extracurricular youth football athletes from Subang Senior High School 2, selected using a total sampling technique. The instrument used to measure aerobic capacity was the Yo-Yo Intermittent Recovery Test Level 1 (YYIR1). Data were analyzed using statistical tests through the SPSS application, including normality tests, homogeneity tests, paired sample t-tests, and independent sample t-tests. Data analysis was carried out through normality tests, homogeneity tests, paired sample t-tests, and independent sample t-tests to determine differences in effects between groups. The results of the study showed, 1) Interval training is effective in increasing VO2max in soccer athletes. 2) Continuous running is also effective in increasing cardiovascular endurance, and 3) There is a substantial difference in the effects between the two methods, with interval training showing greater improvements than continuous running.